Ki67 as a prognostic factor for long-term outcome following surgery in gastrointestinal stromal tumors. Issue 11 (November 2015) - Turkel Kucukmetin, Nurten; Cicek, Bahattin; Saruc, Murat; Ersoy, Ozdal; Vardareli, Eser; Onder, Oguz; Gurluler, Ercument; Tiftikci, Arzu; Goksel, Suha; Tozun, Nurdan
<x xml:space="preserve">Abstract</x> Objective This study aimed to examine the value of Ki67 expression along with other potential prognostic factors for predicting overall survival and disease-free survival in patients with gastrointestinal stromal tumors who underwent curative resection. Patients and methods Sixty-eight histologically confirmed and operated patients with gastrointestinal stromal tumors were included. Clinical and follow-up data were retrieved from medical records and patients were contacted at the end of the study. The effects of certain clinical and histopathological parameters on survival outcomes were examined. Results Sixty-eight patients were followed for a mean duration of follow-up of 2923.3 patient-months. Twelve deaths (17.6%), seven metastasis (10.3%), and two local recurrences (2.9%) occurred. Overall survival was 102.5 months [95% confidence interval (CI), 88.3–116.8] and disease-free survival was 91.8 months (95% CI, 76.5–107.2). Multivariate analyses identified a high Ki67 index (≥10%) as an independent predictor of both poor overall survival (hazard ratio, 4.8; 95% CI 1.2–19.2; P=0.027) and poor disease-free survival (hazard ratio, 15.3; 95% CI, 4.7–50.2). Conclusion A high Ki67 expression seems to be a useful prognostic factor that would aid in predicting disease course in gastrointestinal stromal tumors. These findings deserve further investigation in larger studies.